THE DISTINCTIVE CHARACTERS OF THE NATIONAL LINGUISTIC WORLDVIEW ON THE EXAMPLE OF KARAKALPAK AND ENGLISH LANGUAGES - Muratbaeva Umida Taumuratovna (KONFERENSIYALAR, 2025)
Abstract. Current interested doubted issue in Linguistics is the national linguistic worldview that  many  cognitive  linguists,  ethnolinguistics,  semiotics  and  philosophy  of  language  are investigation  both  national  and  world  linguistic  worldview.  In  essence,  the  national  linguistic worldview  is  a  multidisciplinary  concept  that  touches  on  how  language  shapes  and  depicts  the cultural and mental framework of a nation or community. Every single word spoken by a nation shapes the basic understanding the nations’ notion for other language speakers, that is why it is essential to be aware the representation of linguistic worldview.